The Role of The Multatuli Museum in Teaching Anticolonial History and Culture as The Identity of Banten Society - Tety Suparti; Ajat Sudrajat; Fathurrahman Fathurrahman (Journal of Educational Sciences, 2026)
This study examines the role of the Multatuli Museum in teaching anticolonial history and culture as part of Banten society's identity. The museum, established in 2018 in Rangkasbitung, Lebak Regency, faced initial controversy due to its association with a Dutch colonial figure. Using qualitative methods including observation, interviews, and document analysis, this research investigates how the museum addressed community rejection, the narratives presented through its programs (2018-2020), and strategies for overcoming exhibition space limitations. Findings reveal that the museum employed persuasive and educational approaches to gain acceptance, establishing itself as a center for enhancing historical and cultural literacy. Through non-public programs, public programs, and collaborative initiatives such as the Multatuli Arts Festival, symposiums, and heritage tours, the museum created immersive educational experiences. To address spatial constraints, the museum innovatively utilized virtual platforms, including augmented reality and its official website. This study confirms the Multatuli Museum's significant role as an information and learning center for anticolonial history and culture, integral to Banten's identity formation.